A predictor-corrector infeasible-interior-point method for the Cartesian -LCP over symmetric cones with iteration complexity. (1st December 2016) - Sayadi Shahraki, M.; Mansouri, H.; Zangiabadi, M.
Abstract : In this paper, we present a predictor-corrector infeasible-interior-point method for symmetric cone linear complementarity problem (SCLCP) with the Cartesian -property ( -SCLCP). This method is based on a wide neighbourhood, which is an even wider neighbourhood than the negative infinity neighbourhood. We show that the iteration-complexity bound of the proposed algorithm for a commutative class of search directions is, where is the condition number of matrix G, is the handicap of the problem, r is the rank of the associated Euclidean Jordan algebra and is a given tolerance. To our knowledge, this is the best complexity result obtained so far for the wide neighbourhood infeasible-interior-point methods for the Cartesian -SCLCPs.